Green marketing horizon: Industry sustainability through marketing and innovation - Gonghang Chen; Aemon Sabir; Muhammad Faisal Rasheed; Lucian Belascu; Chi-Wei Su (Journal of Innovation & Knowledge (JIK), 2024)
The UN Sustainable Development Goals (SDGs) emphasize moving the manufacturing sector towards adopting environmentally friendly practices. Manufacturing industries play a critical role in the economic growth of a country; however, they are also associated with directly affecting the environment. Due to limited resources, shifting towards sustainable practices is difficult. The current study examines the effects of green marketing (GM) practices through eco-innovation (EI) to improve the sustainable performance of Pakistan's manufacturing industries. Furthermore, this study also intends to test the moderating effect of circular economy practices on the direct relationship between green market practices and eco-innovation. Responses from 201 professionals working in manufacturing industries were gathered and subjected to structural equation modeling (SEM) analysis to investigate the direct and indirect relationships between the variables in the conceptual model. The results indicate that the green market and eco-innovation have a noteworthy direct impact on SP. Nevertheless, green marketing practices favorably affect sustainable performance by mediating eco-innovation and the positive moderating role of circular economy practices. The current study is relevant for advising managers and policymakers about the potential advantages of supporting sustainable solutions.
Keywords: M31; O30; Q55; Z33; 650; Green marketing (GM); Eco-innovation (EI); Circular economy (CE); Sustainable performance (SP); Pakistan